4-hydroxyisoleucine mediated IGF-1/GLP-1 signalling activation prevents propionic acid-induced autism-like behavioural phenotypes and neurochemical defects in experimental rats. (December 2022) - Bhalla, Sonalika; Mehan, Sidharth
Abstract: Autism is a neuropsychiatric disorder characterized by a neurotransmitter imbalance that impairs neurodevelopment processes. Autism development is marked by communication difficulties, poor socio-emotional health, and cognitive impairment. Insulin-like growth factor-1 (IGF-1) and glucagon-like growth factor-1 (GLP-1) are responsible for regular neuronal growth and homeostasis. Autism progression has been linked to dysregulation of IGF-1/GLP-1 signalling. 4-hydroxyisoleucine (HI), a pharmacologically active amino acid produced from Trigonella foenum graecum, works as an insulin mimic and has neuroprotective properties. The GLP-1 analogue liraglutide (LRG) was employed in our investigation to compare the efficacy of 4-HI in autism prevention. The current study explores the protective effects of 4-HI 50 and 100 mg/kg orally on IGF-1/GLP-1 signalling activation in a PPA-induced experimental model of autism. Propionic acid (PPA) injections to rats by intracerebroventricular (ICV) route for the first 11 days of the experiment resulted in autism-like neurobehavioral, neurochemical, gross morphological, and histopathological abnormalities. In addition, we investigated the dose-dependent neuroprotective effects of 4-HI on the levels of several neurotransmitters and neuroinflammatory cytokines in rat brain homogenate and blood plasma. Neuronal apoptotic and anti-oxidant cellular markers were also studied in blood plasma and brain homogenate samples. Furthermore, the luxol fast blue (LFB) staining results demonstrated significant demyelination in the brains of PPA-induced rats reversed by 4-HI treatment. Rats were assessed for spontaneous locomotor impairments, neuromuscular coordination, stress-like behaviour, learning, and memory to assess neurobehavioral abnormalities. The administration of 4-HI and LRG significantly reversed the behavioural, gross and histological abnormalities in the PPA-treated rat brains. After treatment with 4-HI and LRG, LFB-stained photomicrographs of PPA-treated rats' brains demonstrated the recovery of white matter loss. Our findings indicate that 4-HI protects neurons in rats with autism by enhancing the IGF-1 and GLP-1 protein levels. Highlights: Intracerebral propionic acid infusion causes experimental autism. 4-hydroxyisoleucine (4-HI) improved behavioural and histopathological abnormalities. 4-HI alone and combined with Liraglutide restored neurochemicals in CSF, blood plasma and brain samples. 4-HI exerts neuroprotection by increasing IGF-1 and GLP-1 levels.